Gambling Control by the Jambi City, Indonesia Government from a Good Governance Perspective - Adaliya, Sindi; Sundari, Cici; Armansyah, Yudi (Journal of Governance and Public Policy, 2026)
This study analyzes the Jambi City Government's control over gambling practices from the perspective of good governance. The primary focus of this research is to assess the effectiveness of public policies and inter-agency coordination in responding to the evolving dynamics of gambling practices, including the shift toward online gambling. This research employed a qualitative, exploratory approach. The data used were secondary sources from online media, social media platforms, and relevant scientific journals to examine the Jambi City Government's control over gambling practices from a good governance perspective. Data analysis was conducted qualitatively through document processing and review. The findings indicated that the Jambi City Government's control over gambling practices continues to face significant structural challenges. Empirically, this study revealed that institutional fragmentation, overlapping authorities, and limitations in human resources and budget not only restrict the effectiveness of law enforcement operations but also directly weaken the principles of accountability and institutional capacity within good governance. The shift of gambling practices into the online sphere further exacerbates the weaknesses of integrated oversight mechanisms. These findings refine the good governance framework by demonstrating that failures in cross-agency coordination are a key factor hindering transparency, accountability, and the effectiveness of gambling regulation at the local government level.